Efficacy and safety of bevacizumab in patients with malignant melanoma: a systematic review and PRISMA-compliant meta-analysis of randomized controlled trials and non-comparative clinical studies - Han, Xiao; Ge, Pu; Liu, Siyu; Yang, Dandan; Zhang, Jinzi; Wang, Xinpei; Liang, Weiting (Frontiers in Pharmacology, 2023)
Background: Malignant melanoma is a highly aggressive cancer that spreads and metastasizes quickly. In recent years, the anti-angiogenic drug bevacizumab has been trialed to treat malignant melanoma. We conducted the first meta-analysis to examine the efficacy and safety of bevacizumab combined with other drugs in malignant melanoma. Methods: We searched for randomized controlled trials and non-comparative clinical studies of bevacizumab combined with chemotherapy, targeted medicine, and interferon to treat malignant melanoma in PubMed, Embase, the Cochrane Library, and Web of Science. Meta-analysis of RCT was performed using Review Manager (version 5.4), and non-comparative meta-analysis was performed using R (version 4.0.3). The primary outcome was the objective response rate. Depending on the heterogeneity of the included studies, the pooled outcomes and 95% CI were calculated using either random effects or fixed-effect models. Subgroup outcomes were calculated with possible relevant variables. Sensitivity analyses were carried out by excluding each study from the highly heterogeneous pooled results in turn. The funnel plot and Begg's test were used to test the included studies' potential publication bias. The level of significance was set at p < 0.05. Results: This meta-analysis included 20 trials, including 5 randomized controlled trials and 15 non-comparative clinical studies with a total of 23 bevacizumab intervention arms. In 14 treatment arms, bevacizumab was combined with chemotherapy drugs such as fotemustine, dacarbazine, carboplatin/paclitaxel, and temozolomide. In 6 treatment arms, bevacizumab was combined with targeted medicines such as imatinib, everolimus, sorafenib, erlotinib, and temsirolimus. There were also six treatment arms that used bevacizumab in combination with interferon. The pooled objective response rate was 15.8% (95% CI, 11.4-20.2%). Bevacizumab plus carboplatin/paclitaxel significantly increased the overall survival compared to carboplatin/paclitaxel (HR=0.64, 95% CI, 0.49-0.85, p<0.01). Fatigue, nausea, leukopenia, thrombocytopenia, and neutropenia were the most common adverse events. The pooled incidence of hypertension of all containing bevacizumab arms in malignant melanoma was 32.4% (95% CI, 24.5%-40.3%). Conclusions: This study showed that bevacizumab combined with chemotherapy might be effective and well tolerated in patients with stage III or IV unresectable malignant melanoma.